Risk mitigation for anti software ageing - a systematic literature review - Azman, Thamaratu Izzah; Che Pa, Noraini; Nor, Rozi Nor Haizan; Jusoh, Yusmadi Yah (Little Lion Scientific R&D, 2019)
Software normally undergoes an inevitable ageing process that occurs because of the software performance degradation and the failures of the software to execute. Usually, maintenance process is implemented to eliminate and fix the emergence of errors triggering software failures. The phenomenon also can be slow down and prevented by considering risks exposure through risk mitigation. To achieve anti software ageing, IT organizations need to employ relevant and effective approach to counteract ageing occurrences, thus ensuring optimum software quality and performance from degradation to fit with current and future environmental and technological changes. For this reason, it is significant to ascertain and understand the concepts of anti software ageing and available approaches addressing the issues to identify existing studies limitation and research gaps. This paper conduct a systematic literature review on the studies related to risk mitigation for anti software ageing by following a standard systematic literature review guidelines proposed by Kitchenham (2009). It aims to review the existing current state of research on risk mitigation for anti software ageing. A total 106 studies related to the topic from various journals and conference proceedings has been reviewed. The research in this topic is still active throughout the decade. We noticed that majority of the proposed solution are focusing on implementing software rejuvenation approach to delay ageing occurrences. Throughout findings, technical risk is the most addressed and discussed risk in the literature. The results of this review are significance as a reference on the current trend of research in anti software ageing. Although software rejuvenation are mainly proposed to handle software ageing issues, there are still no clear solutions and guidelines modeled by past researchers to effectively mitigate risks to software ageing especially during software maintenance process and addressing the risks from external risk. Thus, this paper had achieved its aim to review current state of existing research related to risk mitigation for anti software ageing.